1996
DOI: 10.1007/bf02523530
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of tocopherols and phenolic compounds of virgin olive oil

Abstract: The antioxidant effects of hydrophilic phenols and tocopherols on the oxidative stability in virgin olive oils and in purified olive oil have been evaluated. Total hydrophilic phenols and the oleosidic forms of 3,4‐dihydroxyphenolethanol (3,4‐DHPEA) were correlated (r=0.97) with the oxidative stability of virgin olive oil. On the contrary, tocopherols showed low correlation (r=0.05). Purified olive oil with the dialdehydic form of elenolic acid linked to 3,4‐DHPEA, an isomer of oleuropeine aglycon, and 3,4‐DHP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

40
385
3
8

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 494 publications
(444 citation statements)
references
References 12 publications
40
385
3
8
Order By: Relevance
“…The correlation table is not shown in the article due to table number limitations. This is not an unexpected situation since the active phenols in the virgin olive oils are mainly o-diphenols, such as hydroxytyrosol and its oleosidic forms, protocatechuic and caffeic acids (PAPADOPOULOS & BOSKOU, 1991;MONTEDORO et al, 1993;BALDIOLI et al, 1996). These results are in agreement with those reported by BONOLI and co-workers (2004), who found a high correlation between total phenol and o-diphenol (r 2 =0.879, P<0.0001).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The correlation table is not shown in the article due to table number limitations. This is not an unexpected situation since the active phenols in the virgin olive oils are mainly o-diphenols, such as hydroxytyrosol and its oleosidic forms, protocatechuic and caffeic acids (PAPADOPOULOS & BOSKOU, 1991;MONTEDORO et al, 1993;BALDIOLI et al, 1996). These results are in agreement with those reported by BONOLI and co-workers (2004), who found a high correlation between total phenol and o-diphenol (r 2 =0.879, P<0.0001).…”
Section: Resultssupporting
confidence: 91%
“…(BELTRÁN et al, 2005). Oxidative stability, one of the most important quality marker of edible oils, is commonly evaluated by accelerated methods Acta Alimentaria 43,2014 employing relatively high temperatures and air fl ow supply (e.g., Rancimat, active oxygen method, and oxidative stability instrument) (BALDIOLI et al, 1996;APARICIO et al, 1997).…”
mentioning
confidence: 99%
“…Tan et al (2002) found that olive oil with its high initial PV had a longer induction time than other common vegetable oils investigated in his study. The increased oxidative stability of extra virgin olive oil is related to the high levels of monounsaturated oleic acid and the presence of natural antioxidants, especially phenolic compounds (Baldioli et al 1996). Among the investigated oils, pumpkinseed oil, despite its appreciable contents of PUFA and FFA, has the highest oxidative stability.…”
Section: Resultsmentioning
confidence: 99%
“…7 Caffeic acid was not determined in this extract. However, it has been reported to be present in virgin olive oil phenolic fractions 16,17 and its concentration in virgin olive oil is very low (500 lg/kg of oil) (Servili M, unpublished data, 2006).…”
Section: Discussionmentioning
confidence: 99%